Low Altitude Airspace: how enterprises discover a new business dimension - Mozzetti, Chiara; Devitis, Alberto (GEOmedia, 2019)
The development of Low Altitude Airspace activities is a great opportunity for many companies. Work carried out by drones (inspections, surveillance and control, mapping etc.) will be supported by other new activities and services that will pave the way for new business models and revenues. A new set of rules must be set up to allow the correct use of LAAs; UTM projects and U-Space were created for this purpose. Europe is very active in this regard and the Italian U-space project DIODE is an example of highly advanced experimentation. Enterprises are already building large fleets; managing the drones, the people and procedures using advanced platforms that utilize the collected data effectively. Working in compliance with LAA rules is fundamental for success. AI-Crew and AI-Inspection are two innovative platforms born to help Enterprises capitalize on LAA, maximizing their assets.